Pengaruh Kualitas Pelayanan dan Keragaman Produk Terhadap Keputusan Pembelian Konsumen Pada CV Mutiara Permai Cantika Kosmetik Di Gianyar - Ni Luh Putu Astini; Nyoman Dwika Ayu Amrita (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
This study aims to determine the effect partially and simultaneously between service quality and product variety on consumer purchasing decisions at CV Mutiara Permai Cantika in Gianyar. The number of samples was determined by using a non-probability sampling technique of 98 respondents by conducting observations, interviews, questionnaires and literature. The data analysis technique is classical assumption test, multiple linear regression analysis, determination analysis, F-test analysis and t-test analysis. Based on the research results, service quality and product diversity have a positive and significant effect simultaneously and partially on consumer purchasing decisions at CV Mutiara Permai Cantika in Gianyar.